ANALYSIS OF THE LOGIC MODEL APPROACH TO THE PREPARATION OF PERFORMANCE INFORMATION IN THE PLANNING AND BUDGETING PROCESS AT THE BIRO UMUM SEKRETARIAT DAERAH KALIMANTAN UTARA - Rosidah, Siti; Gani, Abdul Juli Andi; Setyowati, Endah (Erudio Journal of Educational Innovation, 2023)
This research aims to describe and analyze in a comprehensive and detailed manner the processes, outcomes, supporting factors, and inhibiting factors for compiling performance information using the Logic Model approach in planning and budgeting at the Biro Umum of the Sekretariat Daerah of North Kalimantan Province. The researcher uses the stages of building a Logic Model from Mclaughlin and Jordan (2015), which consist of gathering relevant information, defining problems and contexts, defining performance elements in tables, drawing models, and involving stakeholders in program verification. The results showed that the process and results of compiling performance planning and budgeting performance information at the Biro Umum of the Sekretariat Daerah of North Kalimantan Province were partly under the stages of building a Logic Model. However, the stages of drawing up the model and involving stakeholders in defining performance and program verification elements had yet to be fulfilled effectively. Existing performance indicators are output-oriented, not outcome-oriented. Recommendations for further research by evaluating the effectiveness of using the Logic Model approach in preparing planning and budgeting performance information.